A novel test method for quantifying cracking propensity of photovoltaic backsheets after ultraviolet exposure. (24th July 2018) - Lin, Chiao‐Chi; Lyu, Yadong; Jacobs, Deborah S.; Kim, Jae Hyun; Wan, Kai‐Tak; Hunston, Donald L.; Gu, Xiaohong
Abstract: Surface cracking in multilayered backsheets is one of the common failure modes for field photovoltaic (PV) modules, leading to safety concerns. However, the current IEC qualification tests such as IEC 61215 cannot adequately predict the backsheet cracking in fielded modules. Moreover, little is known about effect of key environmental factors on the cracking behaviors of backsheets. In this study, a novel test method combining accelerated weathering with in situ surface cracking monitoring during tensile deformation is developed to quantify cracking propensity of backsheets after aging. A polyester‐based backsheet was selected, and 4 environmental conditions (UV/85°C/5% relative humidity (RH), UV/85°C/60% RH, 85°C/5% RH, 85°C/60% RH) were used for backsheet aging. The relationship between material degradation and crack formation of the backsheet under different environmental conditions is discussed. The channel cracks (fragmentation) perpendicular to the loading direction were only observed on the UV‐aged samples, not on those unaged or aged without UV irradiation. Moisture played a synergistic role with UV in the formation of surface cracking. Mode I fracture toughness ( K IC ) of the embrittled surface layer obtained from this test dropped by 98% relative to fresh samples, indicating a much higher cracking propensity of this backsheet after UV exposure. The proposed method was further validated by fragmentation tests of outdoor‐exposed backsheet samples. This method can serve as a quantitative tool to evaluate the cracking propensity of backsheets for a better material selection and lifetime prediction of PV modules. Abstract : We proposed a novel test method by applying tensile deformation on backsheet sample under an in situ surface monitoring instrumentation to quantify the backsheet cracking propensity exposed to different weathering conditions. Surface channel cracks are observed solely in UV‐degraded samples and absent in unaged samples or those aged without UV irradiation. Moisture has played a synergistic role with UV in initiating the surface cracking. Compared to fresh backsheets, the fracture toughness ( K IC ) of the embrittled backsheet surface has dropped by about 98% after exposure to UV humid condition. The relationship between material degradation and cracking behavior of the backsheet is established.